Preparation method and application of high-thermal-conductivity mica paper based on coated mica sheet
By covering the surface of the mica sheet with silica layer to form a core-shell structure, the problem of insufficient thermal conductivity of traditional mica paper is solved, and the thermal conductivity and material density are significantly improved. It is suitable for the main insulation material of large generators and improves the motor Operational reliability.
Patent Information
- Application Number
- CN202411270174.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The thermal conductivity of traditional mica paper is insufficient, resulting in an increase in the main insulation temperature of large generators, limiting the increase in motor capacity and prolonging service life.
The preparation method of coated mica sheets is adopted to form a silicon dioxide layer with a thickness of 5nm to 10nm on the surface of the mica sheets to form a core-shell structure, and the surface chemical modification is performed by sol-gel method to enhance thermal conductivity, and ultrasonic treatment and Vacuum suction filtration to obtain highly thermally conductive mica paper.
It significantly improves the thermal conductivity of mica paper, maintains high breakdown strength, improves the uniformity and density of the material, reduces the interface thermal resistance, and is suitable for the main insulation material of large generators, and improves the operating reliability of the motor.
Smart Images

Figure CN119118138A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermally conductive insulating materials, and in particular to a preparation method and application of high thermal conductive mica paper based on coated mica sheets. Background Art
[0002] Large generators are important equipment in the power transmission system. Their reliable operation is crucial to the stable development of the economy. With the development of science and technology and the advancement of manufacturing technology, large generators are developing towards high voltage and large capacity. However, how to reduce the operating temperature rise of the motor, increase the capacity and extend the service life has always been a bottleneck problem that the motor manufacturing industry urgently needs to solve. Therefore, higher requirements are put forward for the performance of mica tape as the main insulation of large generators, so it is extremely important to study new insulation materials for large generators.
[0003] As the core component of large-capacity high-voltage motors, the main insulation of the stator winding is mainly composed of mica paper, glass fiber cloth and epoxy resin adhesive. However, the thermal conductivity of this insulation system is insufficient, which leads to an increase in the temperature of the main insulation and affects its life, thereby limiting the increase in motor capacity. Mica is an important non-metallic mineral with excellent heat resistance and insulation properties, and is widely used in power equipment. Therefore, the development of a mica insulation system with good thermal conductivity is currently a research hotspot. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the heat cannot be dissipated in time due to the low thermal conductivity of traditional mica paper, and the mica tape cannot be fully impregnated after being doped with high thermal conductivity fillers, and to provide a preparation method and application of high thermal conductivity mica paper based on coated mica sheets.
[0005] The invention discloses high thermal conductivity mica paper based on coated mica sheet. The high thermal conductivity mica paper is a core-shell structure composed of a mica sheet and a silicon dioxide layer coated on the surface of the mica sheet. The thickness of the silicon dioxide layer is 5nm-10nm.
[0006] A method for preparing high thermal conductivity mica paper based on coated mica sheets is carried out according to the following steps:
[0007] Step S1: placing a mica sheet in an organic solvent and then subjecting it to ultrasonic treatment to obtain a mixed solution a;
[0008] Step S2: continuously stirring the mixed solution a obtained in step S1, adding silicon source material, and stirring evenly to obtain a mixed solution b;
[0009] The silicon source material is tetraethyl orthosilicate, and the ratio of the mass of the mica sheet to the volume of tetraethyl orthosilicate is 1g: (50-100)μL;
[0010] Step S3: adjusting the pH value of the mixed solution b obtained in step S2 to 9-10, and stirring evenly to obtain a mixed solution c;
[0011] Step S4: centrifuging the mixed solution c obtained in step S3, collecting the lower layer of precipitate, and drying to obtain mica sheets with surface coated with silicon dioxide;
[0012] Step S5: adding the mica flakes with surface coated with silicon dioxide obtained in step S4 into deionized water, and mixing them thoroughly to obtain mica slurry;
[0013] Step S6: The mica slurry obtained in step S5 is first ultrasonically treated at a frequency of 20kHz to 40kHz for 0.5h to 2h, then sufficiently stirred, and then vacuum filtered at a pressure of -0.03MPa to -0.08MPa, and finally dried to obtain high thermal conductivity mica paper based on coated mica sheets.
[0014] The invention discloses an application of high thermal conductivity mica paper based on coated mica sheets, and the application of the high thermal conductivity mica paper based on coated mica sheets in mica tapes, which are main insulating materials of large generators.
[0015] Beneficial effects of the present invention:
[0016] (1) The present invention uses a sol-gel method to coat an inorganic heat-conducting layer on the surface of a mica sheet and perform surface chemical modification, thereby increasing the compatibility of the surface with the adhesive and reducing the interfacial thermal resistance between the mica sheet and the adhesive. The present invention forms a core-shell structure by coating the mica sheet with silica, thereby making the structure of the composite material more compact, largely ensuring the uniformity of the mica paper during the papermaking process, and providing a mica paper with better thermal conductivity, thereby obtaining a mica paper with an internal thermal conductive network; at the same time, the thermal conductivity of the main material is improved by controlling the thickness of the silica coating layer, thereby not affecting the inherent properties of the main material.
[0017] (2) The method for preparing high thermal conductivity mica paper provided by the present invention requires few equipments, has simple process, low cost, easy operation and is environmentally friendly and pollution-free.
[0018] The present invention can obtain a preparation method and application of high thermal conductivity mica paper based on coated mica sheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 represents a scanning electron microscope image of an uncoated mica sheet;
[0020] Figure 2 A scanning electron microscope image showing the coated mica sheet of the present invention;
[0021] Figure 3 A scanning electron microscope image showing the high thermal conductivity mica paper based on coated mica sheets prepared in the present invention. DETAILED DESCRIPTION
[0022] Specific implementation method 1: This implementation method is a high thermal conductivity mica paper based on a coated mica sheet. The high thermal conductivity mica paper has a core-shell structure consisting of a mica sheet and a silicon dioxide layer coated on the surface of the mica sheet. The thickness of the silicon dioxide layer is 5nm to 10nm.
[0023] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the mass ratio of the mica flakes to silicon dioxide is (80-95):(5-20); the mica flakes are composed of small-particle mica flakes less than 60 mesh, medium-particle mica flakes of 60-80 mesh and large-particle mica flakes of 80-200 mesh, and the mass ratio of the small-particle mica flakes, medium-particle mica flakes and large-particle mica flakes is (20-35):(45-65):(5-10).
[0024] The other steps are the same as those in the first specific implementation.
[0025] Specific implementation method three: This implementation method is a method for preparing high thermal conductivity mica paper based on coated mica sheets, which is carried out according to the following steps:
[0026] Step S1: placing a mica sheet in an organic solvent and then subjecting it to ultrasonic treatment to obtain a mixed solution a;
[0027] By controlling the ultrasonic parameters, the mica flakes can be fully dispersed to facilitate coating.
[0028] Step S2: continuously stirring the mixed solution a obtained in step S1, adding silicon source material, and stirring evenly to obtain a mixed solution b;
[0029] The silicon source material is tetraethyl orthosilicate, and the ratio of the mass of the mica sheet to the volume of tetraethyl orthosilicate is 1g: (50-100)μL;
[0030] By controlling the stirring parameters, the reaction efficiency and coating uniformity are ensured; by controlling the amount of silicon source material, the coating amount of silicon dioxide is controlled.
[0031] Step S3: adjusting the pH value of the mixed solution b obtained in step S2 to 9-10, and stirring evenly to obtain a mixed solution c;
[0032] By controlling the pH value of the mixed solution to be alkaline, the reaction is ensured to proceed thoroughly and the coating efficiency is improved.
[0033] Step S4: centrifuging the mixed solution c obtained in step S3, collecting the lower layer of precipitate, and drying to obtain mica sheets with surface coated with silicon dioxide;
[0034] By controlling the centrifugal parameters, solid-liquid separation is facilitated; by controlling the drying temperature parameters, the solvent is ensured to be completely volatilized.
[0035] Step S5: adding the mica flakes with surface coated with silicon dioxide obtained in step S4 into deionized water, and mixing them thoroughly to obtain mica slurry;
[0036] Step S6: The mica slurry obtained in step S5 is first ultrasonically treated at a frequency of 20kHz to 40kHz for 0.5h to 2h, then sufficiently stirred, and then vacuum filtered at a pressure of -0.03MPa to -0.08MPa, and finally dried to obtain high thermal conductivity mica paper based on coated mica sheets.
[0037] Specific implementation mode four: The difference between this implementation mode and specific implementation modes one to three is that: the ratio of the mass of the mica sheet described in step S1 to the volume of the organic solvent is 1g: (300-500)mL, the organic solvent is composed of ethanol and deionized water, and the volume ratio of the ethanol to the deionized water is (0.5-4): 1; the ultrasonic power in step S1 is 500W-1000W, and the ultrasonic time is 0.5h-2h.
[0038] The other steps are the same as those in Specific Embodiments 1 to 3.
[0039] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that the stirring speeds of the continuous stirring in step S2 and after adding the silicon source material are both 250 rpm to 500 rpm, and the stirring time is both 1 h to 2 h.
[0040] The other steps are the same as those in Specific Embodiments 1 to 4.
[0041] Specific implementation method 6: The difference between this implementation method and specific implementation methods 1 to 5 is that: in step S3, ammonia water is used to adjust the pH value; in step S3, the stirring speed is 250rpm to 500rpm, and the stirring time is 2h to 5h.
[0042] The other steps are the same as those in Specific Embodiments 1 to 5.
[0043] Specific implementation method seven: The difference between this implementation method and specific implementation methods one to six is that: the centrifugal speed in step S4 is 2000rpm~10000rpm, and the centrifugal time is 5min~15min; the drying temperature in step S4 is 60℃~70℃, and the drying time is 8h~12h.
[0044] The other steps are the same as those in Specific Embodiments 1 to 6.
[0045] Specific embodiment eight: The difference between this embodiment and any one of specific embodiments one to seven is that the mass fraction of mica flakes in the mica slurry described in step S5 is 10-20%.
[0046] The other steps are the same as those in Specific Embodiments 1 to 7.
[0047] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that: the stirring in step S6 adopts mechanical stirring, and the stirring time is 20 to 30 minutes; the drying temperature in step S6 is 100 to 120°C.
[0048] The other steps are the same as those in Specific Embodiments 1 to 8.
[0049] Specific implementation method ten: This implementation method provides an application of high thermal conductivity mica paper based on coated mica sheets, and the high thermal conductivity mica paper based on coated mica sheets is used in mica tapes, which are main insulating materials for large generators.
[0050] The following examples are used to verify the beneficial effects of the present invention:
[0051] Example 1: A method for preparing high thermal conductivity mica paper based on coated mica sheets, comprising the following steps:
[0052] Step S1: placing 1 g of mica flakes in 400 mL of an organic solvent, and then ultrasonicating at a power of 500 W for 1 h to obtain a mixed solution a;
[0053] The organic solvent is composed of ethanol and deionized water, and the volume ratio of the ethanol to the deionized water is 1:1;
[0054] Step S2: The mixed solution a obtained in step S1 was continuously stirred at a speed of 400 rpm for 1.5 h, 50 μL of tetraethyl orthosilicate was slowly added, and then the mixture was continuously stirred at a speed of 400 rpm for 2 h to obtain a mixed solution b;
[0055] Step S3: adding ammonia water dropwise to adjust the pH value of the mixed solution b obtained in step S2 to 9-10, and then continuously stirring at a rotation speed of 400 rpm for 5 hours to obtain a mixed solution c;
[0056] Step S4: centrifuging the mixed solution c obtained in step S3 at a speed of 5000 rpm for 10 min, then collecting the lower layer of precipitate, placing it in a vacuum drying oven at a temperature of 60° C. and drying it for 12 h to obtain mica powder with a surface coated with silicon dioxide;
[0057] Step S5: adding the mica powder with surface coated with silicon dioxide obtained in step S4 into deionized water, and mixing them thoroughly to obtain a mica slurry, wherein the mass fraction of mica flakes in the mica slurry is 15%;
[0058] Step S6: The mica slurry obtained in step S5 is first ultrasonically treated at a frequency of 20 kHz for 1 hour, then mechanically stirred for 30 minutes, then vacuum filtered at a pressure of -0.05 MPa, and finally dried at 100° C. to obtain high thermal conductivity mica paper based on coated mica sheets.
[0059] Example 2: A method for preparing high thermal conductivity mica paper based on coated mica sheets, comprising the following steps:
[0060] Step S1: placing 1 g of mica flakes in 400 mL of an organic solvent, and then ultrasonicating at a power of 500 W for 1 h to obtain a mixed solution a;
[0061] The organic solvent is composed of ethanol and deionized water, and the volume ratio of the ethanol to the deionized water is 2:1;
[0062] Step S2: The mixed solution a obtained in step S1 was continuously stirred at a speed of 400 rpm for 1.5 h, 100 μL of ethyl orthosilicate was slowly added, and then continuously stirred at a speed of 400 rpm for 2 h to obtain a mixed solution b;
[0063] Step S3: adding ammonia water dropwise to adjust the pH value of the mixed solution b obtained in step S2 to 9-10, and then continuously stirring at a rotation speed of 400 rpm for 5 hours to obtain a mixed solution c;
[0064] Step S4: centrifuging the mixed solution c obtained in step S3 at a speed of 5000 rpm for 10 min, then collecting the lower layer of precipitate, placing it in a vacuum drying oven at a temperature of 60° C. and drying it for 12 h to obtain mica powder with a surface coated with silicon dioxide;
[0065] Step S5: adding the mica powder with surface coated with silicon dioxide obtained in step S4 into deionized water, and mixing them thoroughly to obtain a mica slurry, wherein the mass fraction of mica flakes in the mica slurry is 15%;
[0066] Step S6: The mica slurry obtained in step S5 is first ultrasonically treated at a frequency of 20 kHz for 1 hour, then mechanically stirred for 30 minutes, then vacuum filtered at a pressure of -0.05 MPa, and finally dried at 100° C. to obtain high thermal conductivity mica paper based on coated mica sheets.
[0067] Example 3: A method for preparing high thermal conductivity mica paper based on coated mica sheets, comprising the following steps:
[0068] Step S1: placing 1 g of mica flakes in 400 mL of an organic solvent, and then ultrasonicating at a power of 500 W for 1 h to obtain a mixed solution a;
[0069] The organic solvent is composed of ethanol and deionized water, and the volume ratio of the ethanol to the deionized water is 0.5:1;
[0070] Step S2: The mixed solution a obtained in step S1 was continuously stirred at a speed of 400 rpm for 1.5 h, 50 μL of tetraethyl orthosilicate was slowly added, and then the mixture was continuously stirred at a speed of 400 rpm for 2 h to obtain a mixed solution b;
[0071] Step S3: adding ammonia water dropwise to adjust the pH value of the mixed solution b obtained in step S2 to 9-10, and then continuously stirring at a rotation speed of 400 rpm for 5 hours to obtain a mixed solution c;
[0072] Step S4: centrifuging the mixed solution c obtained in step S3 at a speed of 5000 rpm for 10 min, then collecting the lower layer of precipitate, placing it in a vacuum drying oven at a temperature of 60° C. and drying it for 12 h to obtain mica powder with a surface coated with silicon dioxide;
[0073] Step S5: adding the mica powder with surface coated with silicon dioxide obtained in step S4 into deionized water, and mixing them thoroughly to obtain a mica slurry, wherein the mass fraction of mica flakes in the mica slurry is 15%;
[0074] Step S6: The mica slurry obtained in step S5 is first ultrasonically treated at a frequency of 20 kHz for 1 hour, then mechanically stirred for 30 minutes, then vacuum filtered at a pressure of -0.05 MPa, and finally dried at 100° C. to obtain high thermal conductivity mica paper based on coated mica sheets.
[0075] Figure 1 represents a scanning electron microscope image of an uncoated mica sheet; Figure 2 The scanning electron microscope image of the coated mica sheet of the present invention is shown; Figure 1-2 As shown, the surface of the uncoated mica sheet is rough, while the surface of the mica sheet coated with silica becomes smooth and uniform.
[0076] Figure 3 The scanning electron microscope image of the high thermal conductivity mica paper based on the coated mica sheet prepared by the present invention is shown; Figure 3 As shown, the mica sheets coated with silica avoid agglomeration, the mica sheets are more densely overlapped with each other, and the thermal conductive path is more efficiently constructed.
[0077] Table 1 shows the performance parameters of high thermal conductivity mica paper in Examples 1-3;
[0078] Table 1
[0079] Thermal conductivity (W / (m·K)) Breakdown strength (kV / mm) Example 1 0.69 14.5 Example 2 0.68 15.8 Example 3 0.65 16.3
[0080] It can be seen from the data in Table 1 that the mica sheet based on the coated type in the present invention significantly improves the thermal conductivity of the mica paper while maintaining a high breakdown strength. With the increase in the amount of tetraethyl orthosilicate added, the heat transfer efficiency between the mica sheets is reduced, and the thermal conductivity of the mica paper decreases slightly. In addition, the presence of the silicon dioxide coating layer improves the dispersibility of the mica sheets, reduces the agglomeration phenomenon, and makes the internal structure of the mica paper more compact, resulting in an increase in the breakdown strength. Therefore, it is proved that the method for preparing high thermal conductivity mica paper based on the coated mica sheet of the present invention can effectively improve the thermal conductivity of the mica tape used for the main insulation of large generators, thereby improving the operating reliability of large generators.
Claims
1. A high thermal conductivity mica paper based on coated mica sheets, characterized in that The high thermal conductivity mica paper is a core-shell structure consisting of a mica sheet and a silicon dioxide layer coated on the surface of the mica sheet, and the thickness of the silicon dioxide layer is 5nm-10nm.
2. The high thermal conductivity mica paper based on coated mica sheet according to claim 1, characterized in that The mass ratio of the mica flakes to silicon dioxide is (80-95):(5-20); the mica flakes are composed of small-particle mica flakes less than 60 meshes, medium-particle mica flakes of 60-80 meshes and large-particle mica flakes of 80-200 meshes, and the mass ratio of the small-particle mica flakes, the medium-particle mica flakes and the large-particle mica flakes is (20-35):(45-65):(5-10).
3. A method for preparing a high thermal conductivity mica paper based on a coated mica sheet as described in any one of claims 1 to 2, characterized in that The preparation method is carried out according to the following steps: Step S1: placing a mica sheet in an organic solvent and then subjecting it to ultrasonic treatment to obtain a mixed solution a; Step S2: continuously stirring the mixed solution a obtained in step S1, adding silicon source material, and stirring evenly to obtain a mixed solution b; The silicon source material is tetraethyl orthosilicate, and the ratio of the mass of the mica sheet to the volume of tetraethyl orthosilicate is 1g: (50-100)μL; Step S3: adjusting the pH value of the mixed solution b obtained in step S2 to 9-10, and stirring evenly to obtain a mixed solution c; Step S4: centrifuging the mixed solution c obtained in step S3, collecting the lower layer of precipitate, and drying to obtain mica sheets with surface coated with silicon dioxide; Step S5: adding the mica flakes with surface coated with silicon dioxide obtained in step S4 into deionized water, and mixing them thoroughly to obtain mica slurry; Step S6: The mica slurry obtained in step S5 is first ultrasonically treated at a frequency of 20kHz to 40kHz for 0.5h to 2h, then sufficiently stirred, and then vacuum filtered at a pressure of -0.03MPa to -0.08MPa, and finally dried to obtain high thermal conductivity mica paper based on coated mica sheets.
4. The method for preparing a high thermal conductivity mica paper based on a coated mica sheet according to claim 3, characterized in that The ratio of the mass of the mica sheet described in step S1 to the volume of the organic solvent is 1g: (300-500)mL, the organic solvent consists of ethanol and deionized water, and the volume ratio of the ethanol to the deionized water is (0.5-4): 1; the ultrasonic power in step S1 is 500W-1000W, and the ultrasonic time is 0.5h-2h.
5. The method for preparing a high thermal conductivity mica paper based on a coated mica sheet according to claim 3, characterized in that The stirring speeds during the continuous stirring in step S2 and after the silicon source material is added are both 250 rpm to 500 rpm, and the stirring time is both 1 h to 2 h.
6. The method for preparing a high thermal conductivity mica paper based on a coated mica sheet according to claim 3, characterized in that In step S3, ammonia water is used to adjust the pH value; in step S3, the stirring speed is 250 rpm to 500 rpm, and the stirring time is 2 h to 5 h.
7. The method for preparing a high thermal conductivity mica paper based on a coated mica sheet according to claim 3, characterized in that In step S4, the centrifugal speed is 2000 rpm to 10000 rpm, and the centrifugal time is 5 min to 15 min; in step S4, the drying temperature is 60° C. to 70° C., and the drying time is 8 h to 12 h.
8. The method for preparing a high thermal conductivity mica paper based on a coated mica sheet according to claim 3, characterized in that The mass fraction of mica flakes in the mica slurry described in step S5 is 10-20%.
9. The method for preparing a high thermal conductivity mica paper based on a coated mica sheet according to claim 3, characterized in that The stirring in step S6 is performed by mechanical stirring, and the stirring time is 20 to 30 minutes; the drying temperature in step S6 is 100 to 120°C.
10. The use of a high thermal conductivity mica paper based on a coated mica sheet as claimed in any one of claims 1 to 2, characterized in that The high thermal conductivity mica paper based on the coated mica sheet is used in mica tape which is the main insulating material of large generators.
Citation Information
Patent Citations
Process for preparing high-dispersibility ultrafine mica powder
CN102732069A
Preparation method for mica paper with high strength, insulation and high temperature resistance
CN109235139A
Preparation method of high-performance composite mica tape for fire-resistant safety cable
CN111118963A
Flaky fine powder, production thereof, and cosmetic
EP0543999A1
KR20190112423A
